Incidence, reversibility, risk factors and the protective effect of high body mass index against sarcopenia in community‐dwelling older Chinese adults. (February 2014) - Yu, Ruby; Wong, Moses; Leung, Jason; Lee, Jenny; Auyeung, Tung Wai; Woo, Jean
Abstract : Aim: We examined the incidence and the reversibility of sarcopenia and their associated factors over a 4‐year period using the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. Methods: A total of 4000 community‐dwelling older adults aged ≥65 years were evaluated for which detailed information regarding demographics, socioeconomic, medical history, lifestyle, and clinical factors were documented at baseline, 2 years, and 4 years later. Sarcopenia was defined according to the EWGSOP algorithm. Incident sarcopenia and its reversibility were documented at each follow‐up year, and related to possible factors. Results: At baseline, of the 4000 participants, 361 (9.0%) had sarcopenia. Between baseline and 2‐year follow‐up, 6.0% of the participants without sarcopenia at baseline had developed sarcopenia, and 18.8% of the initially sarcopenic participants had reverted to normal. Between baseline and 4‐year follow‐up, the corresponding figures were 6.3% and 14.1%, respectively. The average annual incidence over 4 years was 3.1%. After multivariate adjustments, older age, female sex, presence of chronic obstructive pulmonary disease, presence of stroke, higher physical activity levels, presence of instrumental activities of daily living impairments, and lower body mass index were associated with incident sarcopenia, whereas younger age, female sex, higher body mass index and absence of instrumental activities of daily living impairments, but not physical activity, were associated with its reversibility. Protein and vitamin D intake were not significantly associated with sarcopenia incidence or its reversibility. Conclusion: Sarcopenia incidence increases with age, but is potentially reversible in a Chinese elderly population. High body mass index is protective against sarcopenia incidence and its reversibility. Increasing physical activity and maintaining a healthy weight could be beneficial in the prevention of sarcopenia.Geriatr Gerontol Int 2014; 14 (Suppl. 1): 15–28.